Core-shell type graft copolymer particles, production method thereof, and resin composition

Core-shell type graft copolymer particles with increasing crosslinking from the center to the surface of acrylic rubber particles, combined with a compatible shell layer, address the impact resistance issue in thermoplastic resins, resulting in improved mechanical properties.

JP7620453B2Active Publication Date: 2025-01-23KANEKA CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021037972
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-10
Publication Date
2025-01-23
Estimated Expiration
2041-03-10

AI Technical Summary

Technical Problem

Existing acrylic rubber-containing graft copolymers do not adequately enhance the impact resistance of thermoplastic resins like acrylonitrile-styrene resins, necessitating further improvements.

Method used

The development of core-shell type graft copolymer particles with a core composed of agglomerated and enlarged acrylic rubber particles, where the degree of crosslinking increases from the center to the surface, and a shell layer formed from a copolymer containing aromatic vinyl and cyanide vinyl compounds, enhancing compatibility with the matrix resin.

Benefits of technology

The proposed structure significantly improves the impact resistance of thermoplastic resins when blended with these copolymer particles, offering excellent dispersibility and flexibility, leading to enhanced mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620453000002
    Figure 0007620453000002
  • Figure 0007620453000001
    Figure 0007620453000001
Patent Text Reader

Abstract

To provide an acrylic rubber-containing graft copolymer particle which can improve its impact resistance by being blended with a thermoplastic resin.SOLUTION: A core-shell type graft copolymer particle contains a core particle and a shell layer coating the core particle. The core particle contain an agglomerated and grown particle of a rubber particle, and a rubber outer layer coating the agglomerated and grown particle. The rubber particle is composed so that a crosslinking degree on the surface of the particle is higher than a crosslinking degree in the particle. The agglomerated and grown particle is obtained by agglomerating and growing the rubber particle by an acid group-containing polymer. Each of the rubber particle and the rubber outer layer is formed of acrylic rubber obtained by polymerizing a monomer component containing an acrylic monomer and a crosslinkable monomer. The shell layer is formed of a copolymer containing an aromatic vinyl compound unit and a vinyl cyanide compound unit.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to core-shell type graft copolymer particles, a method for producing the same, and a resin composition containing the particles. [Background technology]

[0002] ABS resin (acrylonitrile-butadiene-styrene) has excellent rigidity, impact resistance, and heat deformation resistance, so it is widely used in various miscellaneous goods, interior and exterior materials for automobiles, housing parts for home appliances such as rice cookers, microwave ovens, and vacuum cleaners, and housings and parts for office equipment such as telephones and facsimiles. However, it has the disadvantage of being poorly weatherable.

[0003] In order to improve the weather resistance of ABS resin, ASA resin (acrylonitrile-styrene-acrylic) has been developed, in which the rubber component of ABS resin has been changed from butadiene rubber, which is unstable against light and heat, to acrylic rubber, which is relatively stable. However, ASA resin has the problem that it is difficult to develop impact resistance compared to ABS resin.

[0004] Patent Document 1 describes the blending of a graft copolymer obtained by graft polymerizing an aromatic vinyl monomer, a vinyl cyanide monomer, or an unsaturated acid ester monomer in the presence of crosslinked acrylic acid ester rubber particles with an acrylonitrile-styrene resin.

[0005] Patent Document 2 describes that an acrylic graft copolymer (A) obtained by polymerizing a monomer selected from the group consisting of vinyl cyanide compounds, aromatic vinyl compounds, and (meth)acrylic acid alkyl esters onto an acrylic rubber polymer, and a diene graft copolymer (B) obtained by polymerizing the monomer onto a diene rubber polymer are blended into an acrylonitrile-styrene resin. The document describes that the diene rubber polymer may be coagulated and enlarged using an acid group-containing latex. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 58-222139 [Patent Document 2] JP 2013-221116 A Summary of the Invention [Problem to be solved by the invention]

[0007] When a graft copolymer containing an acrylic rubber is blended with a thermoplastic resin such as an acrylonitrile-styrene resin, the impact resistance of the resin can be improved, but further improvements are required.

[0008] In view of the above-mentioned current situation, the present invention aims to provide acrylic rubber-containing graft copolymer particles that can be blended with a thermoplastic resin to improve the impact resistance of the resin, a method for producing the particles, and a resin composition containing the particles.

[0009] The present inventors have found that the above problems can be solved by adopting a specific structure for the acrylic rubber contained in the acrylic-rubber-containing graft copolymer particles, and have arrived at the present invention.

[0010] That is, the present invention relates to a core-shell type graft copolymer particle comprising a core particle and a shell layer covering the core particle, the core particle comprising an agglomerated thickened particle of rubber particles and a rubber outer layer covering the agglomerated thickened particle, the rubber particles being configured so that the degree of crosslinking at the surface of the particle is higher than the degree of crosslinking inside the particle, the agglomerated thickened particle being formed by agglomerating and thickening the rubber particles with an acid group-containing polymer, the rubber particles and the rubber outer layer being formed from an acrylic rubber obtained by polymerizing a monomer component containing an acrylic monomer and a crosslinkable monomer, respectively, and the shell layer being formed from a copolymer containing an aromatic vinyl compound unit and a vinyl cyanide compound unit. Preferably, the rubber particles are configured so that the degree of cross-linking increases from the center to the surface of the particle. Preferably, the rubber particle includes a rubber particle core layer located at the center of the rubber particle and a rubber particle surface layer located on the surface of the rubber particle, and the rubber particle surface layer has a higher degree of crosslinking than the rubber particle core layer. More preferably, the rubber particle further includes a rubber particle intermediate layer located between the rubber particle core layer and the rubber particle surface layer. Preferably, the acid group-containing polymer is a polymer containing a carboxyl group-containing vinyl monomer unit. Preferably, the ratio of the core particles to the core-shell type graft copolymer particles is 66 to 90% by weight. Preferably, the core particles have a volume average particle size of 400 to 1200 nm. The present invention also relates to a method for producing core-shell graft copolymer particles comprising core particles and a shell layer covering the core particles, the method comprising the steps of: polymerizing a monomer component containing an acrylic monomer and a crosslinkable monomer to form rubber particles configured such that the degree of crosslinking on the surface of the particles is higher than the degree of crosslinking inside the particles; agglomerating and enlarging the rubber particles with an acid group-containing polymer latex to obtain aggregated and enlarged particles of rubber particles; polymerizing a monomer component containing an acrylic monomer and a crosslinkable monomer in the presence of the aggregated and enlarged particles to form a rubber outer layer covering the aggregated and enlarged particles, thereby obtaining core particles comprising the aggregated and enlarged particles and the rubber outer layer; and copolymerizing a monomer component containing an aromatic vinyl compound and a vinyl cyanide compound in the presence of the core particles to form a shell layer covering the core particles, thereby obtaining the core-shell graft copolymer particles. Preferably, in the step of forming the rubber particles, the ratio of the crosslinkable monomer to the monomer component is increased over time to form rubber particles having a higher degree of crosslinking from the center to the surface of the rubber particles. Preferably, in the step of forming the rubber particles, a monomer component including an acrylic monomer and a cross-linkable monomer are polymerized in multiple stages to form rubber particles including a rubber particle core layer and a rubber particle surface layer having a higher degree of cross-linking than the rubber particle core layer. Preferably, the acid group-containing polymer is a polymer containing a carboxyl group-containing vinyl monomer unit. The present invention further relates to a resin composition comprising 100 parts by weight of a thermoplastic resin which is a copolymer containing an aromatic vinyl compound unit and a vinyl cyanide compound unit, and 10 to 100 parts by weight of the core-shell type graft copolymer particles, or a molded article obtained by molding the resin composition. Effect of the Invention

[0011] According to the present invention, it is possible to provide acrylic rubber-containing graft copolymer particles that can be blended with a thermoplastic resin to improve the impact resistance of the resin, a method for producing the particles, and a resin composition containing the particles. [Brief description of the drawings]

[0012] [Figure 1] A process diagram illustrating a process for producing core-shell type graft copolymer particles according to a preferred embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described in detail. <Core-shell type graft copolymer particles> The core-shell graft copolymer particles according to the present disclosure have a core-shell structure including a core particle and a shell layer covering the core particle. The core particle refers to a particle located inside the core-shell graft copolymer particle. On the other hand, the shell layer refers to a polymer layer located on the surface side of the core-shell graft copolymer particle and covering the surface of the core particle, and is also called a graft layer. The shell layer covers the surface of the core particle, but is not limited to one that covers the entire surface of the core particle, and it is sufficient that the shell layer covers at least a part of the surface of the core particle. In FIG. 1, the core-shell graft copolymer particles are designated by reference numeral 24 , the core particles by reference numeral 23 , and the shell layer by reference numeral 15 .

[0014] <Core particle> The core particle includes an aggregated thickening particle of rubber particles and a rubber outer layer covering the aggregated thickening particle. Here, rubber means a polymer having a crosslinked structure (hereinafter, also referred to as a crosslinked polymer). Since the core particle is formed from a crosslinked polymer, it is possible to impart impact resistance to the matrix resin by blending the core-shell type graft copolymer particles with the matrix resin. In FIG. 1, the rubber particles are indicated by reference numeral 21, the aggregated and enlarged particles of the rubber particles are indicated by reference numeral 22, the outer rubber layer is indicated by reference numeral 14, and the core particles are indicated by reference numeral 23.

[0015] The crosslinked polymers forming the rubber particles and the outer rubber layer are acrylic rubbers obtained by polymerizing a monomer component containing an acrylic monomer and a crosslinkable monomer. The crosslinked polymers forming the rubber particles and the crosslinked polymers forming the outer rubber layer may be the same or different. It is preferable that the core particles are composed only of acrylic rubbers and do not contain siloxane rubbers or butadiene rubbers.

[0016] The acrylic monomer is not particularly limited, but examples thereof include acrylic acid alkyl esters such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, dodecyl acrylate, stearyl acrylate, and behenyl acrylate; aromatic ring-containing acrylates such as phenoxyethyl acrylate and benzyl acrylate; hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate; glycidyl acrylates such as glycidyl acrylate and glycidyl alkyl acrylate; alkoxyalkyl acrylates, etc. Only one type of acrylic monomer may be used, or two or more types may be used in combination.

[0017] The acrylic monomer is preferably an alkyl acrylate. The number of carbon atoms in the alkyl group of the alkyl acrylate is preferably 1 to 22, more preferably 1 to 18, even more preferably 2 to 12, and still more preferably 2 to 6. Butyl acrylate is particularly preferable as the acrylic monomer.

[0018] The monomer component forming the acrylic rubber may be composed of only the acrylic monomer, or may contain another monomer having one unsaturated bond per molecule that is copolymerizable with the acrylic monomer. The other monomer is not particularly limited, but examples thereof include methacrylic monomers, aromatic vinyl compounds, vinyl cyanide compounds, vinyl halide compounds such as vinyl chloride and chloroprene, vinyl acetate, and alkenes such as ethylene and propylene.

[0019] In the monomer components (excluding crosslinkable monomers) forming the acrylic rubber, the content of the acrylic monomer is preferably 50 to 100% by weight, more preferably 70 to 100% by weight, even more preferably 80 to 100% by weight, still more preferably 90 to 100% by weight, and particularly preferably 95 to 100% by weight.

[0020] The crosslinkable monomer used to form the acrylic rubber is a compound having two or more unsaturated bonds in one molecule that can be copolymerized with the acrylic monomer. Specific examples include, but are not limited to, (meth)acrylates having an allyl group, such as allyl (meth)acrylate, allyl alkyl (meth)acrylate, and allyloxy alkyl (meth)acrylate; polyfunctional (meth)acrylates having two or more (meth)acrylic groups, such as (poly)ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene. Among these, allyl methacrylate, triallyl isocyanurate, butanediol di(meth)acrylate, and divinylbenzene are preferred, and allyl methacrylate is particularly preferred. The crosslinkable monomer may be used alone or in combination of two or more. Note that (meth)acrylic is a collective term for acrylic and methacrylic.

[0021] The ratio of the core particles to the core-shell graft copolymer particles is preferably 60% by weight or more, more preferably 65% ​​by weight or more. In particular, since excellent impact resistance can be exhibited, it is preferably 66% by weight or more, more preferably 68% by weight or more, and even more preferably 69% by weight or more. The upper limit of the ratio is preferably 90% by weight or less, more preferably 85% by weight or less, even more preferably 80% by weight or less, even more preferably 78% by weight or less, and particularly preferably 76% by weight or less.

[0022] From the viewpoint of impact resistance, the volume average particle diameter of the core particles is preferably 200 nm or more, more preferably 300 nm or more. In particular, since excellent impact resistance can be exhibited, it is preferably 400 nm or more, more preferably 500 nm or more, even more preferably 600 nm or more, and particularly preferably 700 nm or more. The upper limit of the volume average particle diameter is not particularly limited, but from the viewpoint of productivity, it is preferably 1200 nm or less, more preferably 1000 nm or less, even more preferably 900 nm or less, and particularly preferably 800 nm or less. The volume average particle diameter of the core particles is a value measured by using a particle diameter measuring device in the state of the latex of the polymer particles, as shown in the Examples section. The particle diameter of the core particles can be controlled by the type and amount of the acid group-containing polymer, initiator, reducing agent, emulsifier, etc., polymerization temperature, polymerization time, etc.

[0023] <Rubber particles> The rubber particles are configured so that the degree of crosslinking on the surface of the particles is higher than the degree of crosslinking inside the particles. By adopting such a specific configuration for the degree of crosslinking of the rubber particles, it is possible to significantly improve the impact resistance of the thermoplastic resin by blending the core-shell type graft copolymer particles. The degree of crosslinking refers to the density of the crosslinked structure introduced into the polymer by the crosslinkable monomer. The degree of crosslinking can be controlled by adjusting the ratio of the amount of crosslinkable monomer to the amount of monomer component, and the higher the ratio of the amount of crosslinkable monomer, the higher the degree of crosslinking.

[0024] According to one aspect of this embodiment, the rubber particles are configured so that the degree of crosslinking increases from the center of the particle toward the surface. The degree of crosslinking may be configured so that it increases continuously or discontinuously. Such rubber particles can be realized by controlling the addition of the monomer component and the crosslinkable monomer when forming the rubber particles so that the ratio of the amount of the crosslinkable monomer to the amount of the monomer component increases over time.

[0025] In this embodiment, the amount of the crosslinkable monomer is preferably adjusted within a range of 0.001 to 10 parts by weight relative to 100 parts by weight of the monomer components constituting the rubber particles, more preferably 0.01 to 5 parts by weight, even more preferably 0.05 to 3 parts by weight, and particularly preferably 0.1 to 1 part by weight.

[0026] According to another aspect of this embodiment, the rubber particles have a multi-layer structure composed of at least two layers, and the degree of cross-linking in each layer is adjusted so that the degree of cross-linking on the surface of the rubber particles is higher than the degree of cross-linking inside the rubber particles. Specifically, the rubber particles include at least a rubber particle core layer located at the center of the particle and a rubber particle surface layer located on the surface of the particle, and the rubber particle surface layer is configured to have a higher degree of cross-linking than the rubber particle core layer.

[0027] The rubber particles may have a two-layer structure consisting of only a central layer of the rubber particle and a surface layer of the rubber particle. However, the rubber particles may further include at least one intermediate layer between the rubber particle core layer and the rubber particle surface layer. In this case, it is preferable that the surface layer of the rubber particles has a higher degree of cross-linking than the intermediate layer of the rubber particles, and the intermediate layer of the rubber particles has a higher degree of cross-linking than the rubber particle core layer.

[0028] The upper part of Fig. 1 shows the formation of a three-layer structure rubber particle 21. The central layer of the rubber particle is indicated by reference numeral 11, the intermediate layer of the rubber particle by reference numeral 12, and the surface layer of the rubber particle by reference numeral 13. However, the intermediate layer of the rubber particle may have two or more layers, that is, the rubber particle may have a structure of four or more layers.

[0029] In the core-shell graft copolymer particles according to another embodiment, the types or amounts of monomer components constituting each layer and the types of crosslinkable monomers used in each layer may be the same or different.

[0030] In this embodiment, the amount of the crosslinkable monomer used in each layer is preferably selected within the range of 0.001 to 10 parts by weight relative to 100 parts by weight of the monomer components constituting each layer, more preferably 0.01 to 5 parts by weight, even more preferably 0.05 to 3 parts by weight, and particularly preferably 0.1 to 1 part by weight.

[0031] More specifically, the amount of the crosslinkable monomer used in the rubber particle core layer is preferably 0.001 to 3 parts by weight, more preferably 0.01 to 2 parts by weight, even more preferably 0.05 to 1 part by weight, and even more preferably 0.1 to 0.3 parts by weight, relative to 100 parts by weight of the monomer components constituting the rubber particle core layer.

[0032] In addition, the amount of the crosslinkable monomer used in the surface layer of the rubber particle is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, even more preferably 0.2 to 3 parts by weight, and even more preferably 0.3 to 1 part by weight, relative to 100 parts by weight of the monomer components constituting the surface layer of the rubber particle.

[0033] The amount of the crosslinkable monomer used in the intermediate layer of the rubber particle is preferably greater than the amount of the crosslinkable monomer used in the core layer of the rubber particle and less than the amount of the crosslinkable monomer used in the surface layer of the rubber particle.

[0034] <Agglomerated rubber particles> The term "agglomerated rubber particles" refers to the above-mentioned rubber particles that have been agglomerated and agglomerated by an acid group-containing polymer. Although details will be described later, rubber particles can be agglomerated and agglomerated by adding a latex of an acid group-containing polymer to a system containing rubber particles. At this time, multiple rubber particles agglomerate, and the particle size can be enlarged by approximately several times. The middle part of Figure 1 shows, as a conceptual diagram, multiple rubber particles 21 agglomerate to form an agglomerated rubber particle 22.

[0035] <Acid group-containing polymer> The acid group-containing polymer that causes the rubber particles to aggregate and grow refers to a polymer having a functional group that exhibits acidity. The functional group that exhibits acidity is not particularly limited, but a carboxyl group is preferred. The acid group-containing polymer is preferably a polymer containing a carboxyl group-containing vinyl monomer unit, and more preferably a copolymer of a carboxyl group-containing vinyl monomer and a vinyl monomer unit that does not have a carboxyl group. Examples of the carboxyl group-containing vinyl monomer include acrylic acid, methacrylic acid, itaconic acid, and crotonic acid. Of these, acrylic acid and methacrylic acid are preferred. Only one type of acid group-containing polymer may be used, or two or more types may be used in combination.

[0036] As the acid group-containing polymer, from the viewpoints of ease of aggregation and enlargement and thermal stability of the resin, a polymer obtained by polymerizing 5 to 30% by weight of one or more carboxyl group-containing vinyl monomers, 25 to 95% by weight of one or more (meth)acrylic acid alkyl esters having an alkyl group with a carbon number of 1 to 12, and 0 to 60% by weight of other copolymerizable vinyl monomers is preferred.

[0037] The one or more (meth)acrylic acid alkyl esters having an alkyl group with 1 to 12 carbon atoms include esters of acrylic acid and an alcohol having a straight or branched chain with 1 to 12 carbon atoms, and esters of methacrylic acid and an alcohol having a straight or branched chain with 1 to 12 carbon atoms. From the viewpoint of production stability, the number of carbon atoms in the alkyl group is preferably 1 to 8. Specific examples include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, etc. These may be used alone or in combination of two or more.

[0038] The other copolymerizable vinyl monomer is not particularly limited, and examples thereof include aromatic vinyl compounds such as styrene, α-methylstyrene, and p-methylstyrene; vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; and polyfunctional vinyl monomers having two or more polymerizable vinyl groups in one molecule such as allyl methacrylate, polyethylene glycol dimethacrylate, triallyl cyanurate, triallyl isocyanurate, and triallyl trimellitate. These may be used alone or in combination of two or more kinds.

[0039] Particularly from the viewpoint of ease of aggregation and growth and production stability, the acid group-containing polymer according to a preferred embodiment is obtained by polymerizing 5 to 25% by weight of one or more carboxyl group-containing vinyl monomers selected from the group consisting of acrylic acid, methacrylic acid, itaconic acid, and crotonic acid, 25 to 95% by weight of one or more (meth)acrylic acid alkyl esters having an alkyl group with a carbon number of 1 to 12, and 0 to 60% by weight of one or more other vinyl monomers selected from the group consisting of aromatic vinyl compounds, vinyl cyanide compounds, and polyfunctional vinyl monomers.

[0040] <Rubber outer layer> The core-shell type graft copolymer particle according to the present disclosure includes a rubber outer layer that covers the above-mentioned aggregated thickened particle of rubber particles. The core particle is composed of the aggregated thickened particle of rubber particles and the rubber outer layer. In FIG. 1, the aggregated thickened particle of rubber particles is indicated by reference numeral 22, the rubber outer layer by reference numeral 14, and the core particle by reference numeral 23. The rubber outer layer covers the surface of the aggregated thickened particle, but is not limited to covering the entire surface of the aggregated thickened particle, and it is sufficient that the rubber outer layer covers at least a part of the surface of the aggregated thickened particle. As described above, the outer rubber layer is formed from an acrylic rubber obtained by polymerizing a monomer component containing an acrylic monomer and a crosslinkable monomer.

[0041] From the viewpoint of improving impact resistance, the degree of crosslinking of the outer rubber layer is preferably higher than the degree of crosslinking of the surface of the rubber particle (or the degree of crosslinking of the surface layer of the rubber particle). The amount of the crosslinkable monomer used in the outer rubber layer is not particularly limited, but is preferably 0.1 to 20 parts by weight, more preferably 1 to 18 parts by weight, further preferably 3 to 15 parts by weight, and more preferably 5 to 12 parts by weight, relative to 100 parts by weight of the monomer component constituting the outer rubber layer.

[0042] From the viewpoint of impact resistance, the proportion of the rubber outer layer in the core particle is preferably 1 to 50% by weight, more preferably 2 to 40% by weight, even more preferably 3 to 30% by weight, even more preferably 4 to 20% by weight, and particularly preferably 5 to 15% by weight.

[0043] (Shell layer) The shell layer is a polymer layer that covers the surface of the core particle and is the outermost layer of the graft copolymer particle. The shell layer is preferably graft-bonded to the core particle, but may also include a shell layer that is not graft-bonded. The shell layer improves the compatibility between the graft copolymer particle and the matrix resin, and allows the graft copolymer particle to be dispersed in the resin composition in the form of primary particles. The shell layer may be composed of a single layer or multiple layers having different compositions.

[0044] The shell layer is formed from a copolymer containing an aromatic vinyl compound unit and a vinyl cyanide compound unit in order to improve compatibility with the matrix resin. The copolymer may further contain a (meth)acrylic acid ester unit.

[0045] The aromatic vinyl compound is not particularly limited, but examples thereof include styrene, α-methylstyrene, p-methylstyrene, p-isopropylstyrene, o-chlorostyrene, p-chlorostyrene, dichlorostyrene, etc. Among these, styrene is preferred.

[0046] The vinyl cyanide compound is not particularly limited, but examples thereof include acrylonitrile, methacrylonitrile, etc. Among these, acrylonitrile is preferred.

[0047] The (meth)acrylic acid ester is not particularly limited, but examples thereof include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; aromatic ring-containing (meth)acrylates such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate; glycidyl (meth)acrylate and glycidyl alkyl (meth)acrylate; and alkoxyalkyl (meth)acrylates.

[0048] From the viewpoint of compatibility with the matrix resin, the proportion of the aromatic vinyl compound unit in the entire copolymer constituting the shell layer is preferably 30 to 95% by weight, more preferably 50 to 90% by weight, further preferably 60 to 85% by weight, and particularly preferably 70 to 82% by weight. The proportion of the vinyl cyanide compound unit is preferably 5 to 70% by weight, more preferably 10 to 50% by weight, further preferably 15 to 40% by weight, and particularly preferably 18 to 30% by weight.

[0049] The shell layer may be formed from a copolymer having a crosslinked structure, but is preferably formed from a copolymer having no crosslinked structure, i.e., the shell layer is preferably formed from a polymer synthesized without using a crosslinkable monomer.

[0050] <Method for producing core-shell type graft copolymer particles> The method for producing the graft copolymer particles is not particularly limited, but for example, emulsion polymerization, mini-emulsion polymerization, micro-emulsion polymerization, and emulsifier-free (soap-free) emulsion polymerization can be used, among which emulsion polymerization is preferred.

[0051] The emulsifier that can be used in the emulsion polymerization is not particularly limited, and may be an anionic surfactant, a nonionic surfactant, a cationic surfactant, an amphoteric surfactant, etc. Also, a dispersant such as polyvinyl alcohol, alkyl-substituted cellulose, polyvinylpyrrolidone, or a polyacrylic acid derivative may be used in combination.

[0052] The anionic surfactant is not particularly limited, and examples thereof include the following compounds: fatty acid soaps such as potassium laurate, potassium coconut fatty acid, potassium myristate, potassium oleate, potassium oleate diethanolamine salt, sodium oleate, potassium palmitate, potassium stearate, sodium stearate, mixed fatty acid soda soap, semi-hardened beef tallow fatty acid soda soap, and castor oil potassium soap; alkyl sulfates such as sodium dodecyl sulfate, sodium higher alcohol sulfate, triethanolamine dodecyl sulfate, ammonium dodecyl sulfate, sodium polyoxyethylene alkyl ether sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, and sodium 2-ethylhexyl sulfate; Acid ester salts; sodium alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate; sodium dialkylsulfosuccinates such as sodium di-2-ethylhexylsulfosuccinate; sodium alkylnaphthalenesulfonates; sodium alkyldiphenyletherdisulfonates; potassium alkylphosphate salts; phosphate ester salts such as sodium polyoxyethylene lauryl ether phosphate; sodium salts of naphthalenesulfonic acid formalin condensates; polycarboxylate type polymeric anions; sodium acyl (beef tallow) methyl taurate; sodium acyl (coconut) methyl taurate; sodium cocoyl isethionate; sodium α-sulfofatty acid ester salts; sodium amidoethersulfonate; oleyl sarcosine; sodium lauroyl sarcosine; rosin acid soap, etc.

[0053] The nonionic surfactant is not particularly limited, and examples thereof include the following compounds: polyoxyethylene alkyl allyl ethers or polyoxyethylene alkyl ethers such as polyoxyethylene nonylphenyl ether, polyoxyethylene oleyl ether, and polyoxyethylene lauryl ether; polyoxyethylene sorbitan esters such as polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan monostearate; polyoxyethylene fatty acid esters such as polyethylene glycol monolaurate, polyethylene glycol monostearate, and polyethylene glycol monooleate; and oxyethylene / oxypropylene block copolymers.

[0054] The cationic surfactant is not particularly limited, and examples thereof include the following compounds: alkylamine salts such as coconut amine acetate, stearyl amine acetate, octadecyl amine acetate, and tetradecyl amine acetate; and quaternary ammonium salts such as lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, cetyl trimethyl ammonium chloride, distearyl dimethyl ammonium chloride, alkyl benzyl dimethyl ammonium chloride, hexadecyl trimethyl ammonium chloride, and behenyl trimethyl ammonium chloride.

[0055] The amphoteric surfactant is not particularly limited, but examples thereof include the following compounds: alkyl betaines such as lauryl betaine, stearyl betaine, and dimethyl lauryl betaine; sodium lauryl diaminoethyl glycine; amido betaine; imidazoline; lauryl carboxymethyl hydroxyethyl imidazolinium betaine, and the like.

[0056] These emulsifiers may be used alone or in combination of two or more. As the emulsifier, sodium dialkyl sulfosuccinate or a surfactant having an oxyethylene structure is preferred, and sodium polyoxyethylene lauryl ether phosphate is particularly preferred. By adjusting the amount of the emulsifier used, the average particle size of the polymer particles can be controlled.

[0057] When the emulsion polymerization method is employed, known polymerization initiators, such as 2,2'-azobisisobutyronitrile, hydrogen peroxide, potassium persulfate, and ammonium persulfate, can be used as thermal decomposition initiators.

[0058] Also usable is a redox type initiator obtained by using a peroxide such as an organic peroxide, such as t-butyl peroxyisopropyl carbonate, paramenthane hydroperoxide, cumene hydroperoxide, dicumyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, or t-hexyl peroxide; or an inorganic peroxide, such as hydrogen peroxide, potassium persulfate, or ammonium persulfate, in combination with at least one reducing agent selected from the group consisting of sodium formaldehyde sulfoxylate, glucose, transition metal salts, such as iron (II) sulfate, chelating agents, such as disodium ethylenediaminetetraacetate, or pyrophosphates, such as sodium pyrophosphate, or the like.

[0059] When a redox type initiator is used, polymerization can be performed even at a low temperature where the peroxide does not substantially decompose thermally, and the polymerization temperature can be set in a wide range, which is preferable. Among them, organic peroxides such as cumene hydroperoxide, dicumyl peroxide, and t-butyl hydroperoxide are preferably used as the redox type initiator. The amount of the initiator used, and the amount of the reducing agent, transition metal salt, chelating agent, etc. used when a redox type initiator is used may be within a known range. In addition, when polymerizing the crosslinkable monomer, a known chain transfer agent can be used in a known amount. A surfactant can be additionally used, which is also within a known range.

[0060] The solvent used during emulsion polymerization may be any solvent that allows the emulsion polymerization to proceed stably, and for example, water can be suitably used.

[0061] The temperature during emulsion polymerization is not particularly limited as long as the emulsifier is uniformly dissolved in the solvent, but is, for example, 40 to 75°C, preferably 45 to 70°C, and more preferably 49 to 65°C.

[0062] Specifically, the core-shell type graft copolymer particles according to the present disclosure can be produced by carrying out the following steps (I) to (IV) in this order. Step (I): First, in the presence of an emulsifier and an initiator, a monomer component including an acrylic monomer and a crosslinkable monomer are polymerized to form rubber particles configured so that the degree of crosslinking on the surface of the particles is higher than the degree of crosslinking inside the particles.

[0063] According to one aspect of this embodiment, in step (I), polymerization is carried out while adding a monomer component and a crosslinkable monomer to the reaction system, and the amounts of the monomer component and the crosslinkable monomer added are controlled so that the ratio of the crosslinkable monomer to the monomer component increases over time. This makes it possible to form rubber particles in which the degree of crosslinking increases from the center of the rubber particle toward the surface. The ratio of the crosslinkable monomer to the monomer component may be increased continuously or discontinuously. It may also be increased linearly or nonlinearly. The monomer component and the crosslinkable monomer may be added separately, or may be added as a mixture of both.

[0064] According to another aspect of this embodiment, in step (I), a monomer component containing an acrylic monomer and a crosslinkable monomer are polymerized in multiple stages to form rubber particles including at least a rubber particle central layer located at the center of the particle and a rubber particle surface layer located on the surface of the particle. At this time, by setting the ratio of the crosslinkable monomer to the monomer component when forming the rubber particle surface layer higher than the ratio of the crosslinkable monomer to the monomer component when forming the rubber particle central layer, a rubber particle surface layer having a higher degree of crosslinking than the rubber particle central layer can be formed.

[0065] The multi-stage polymerization can also form a rubber particle intermediate layer between the rubber particle core layer and the rubber particle surface layer. In this case, it is preferable to set the ratio of the crosslinkable monomer to the monomer components when forming the rubber particle intermediate layer higher than the ratio of the crosslinkable monomer to the monomer components when forming the rubber particle core layer, and to set the ratio of the crosslinkable monomer to the monomer components when forming the rubber particle surface layer higher than the ratio when forming the rubber particle intermediate layer.

[0066] Step (II): Next, an acid group-containing polymer latex is added to the system containing the rubber particles, and the rubber particles are coagulated and enlarged by the acid group-containing polymer latex to obtain coagulated and enlarged particles of the rubber particles. The acid group-containing polymer latex can be produced by emulsion polymerization, the details of which are the same as those of the emulsion polymerization in the production of the core-shell type graft copolymer particles described above. It is preferable to adjust the pH of a system containing rubber particles (for example, a latex of rubber particles) to 10 or less before adding the acid group-containing polymer latex.

[0067] From the viewpoints of impact resistance and production stability, the amount of the acid group-containing polymer added is preferably 0.1 to 15 parts by weight, more preferably 0.3 to 10 parts by weight, and even more preferably 0.5 to 8 parts by weight, based on 100 parts by weight of the solid content of the rubber particles. The solid content concentration of the latex of the rubber particles during coagulation and thickening is preferably 10 to 50% by weight, and more preferably 15 to 45% by weight, from the viewpoint of controlling the coagulation and thickening characteristics.

[0068] In order to sufficiently promote the aggregation and enlargement of rubber particles, it is preferable to add an alkali such as sodium hydroxide or potassium hydroxide after adding a latex of an acid group-containing polymer to a system containing rubber particles, and further to uniformly stir the mixture for, for example, about 10 minutes to 3 hours. By increasing the pH of the system by adding an alkali, the particle size of the acid group-containing polymer in the latex becomes large, and the aggregation and enlargement of rubber particles therein becomes easy to proceed. In addition, the temperature of the system during stirring may be room temperature, but from the viewpoint of controlling the aggregation and enlargement characteristics, it is preferably 35 to 85°C, more preferably 40 to 80°C.

[0069] Step (III): Next, a monomer component containing an acrylic monomer, a crosslinkable monomer, and an initiator, if necessary, are added to the system containing the agglomerated enlarged particles of the rubber particles, and the monomer component and the crosslinkable monomer are polymerized in the presence of the agglomerated enlarged particles to form a rubber outer layer that covers the agglomerated enlarged particles, thereby obtaining core particles containing the agglomerated enlarged particles and the rubber outer layer.

[0070] Step (IV): Next, a monomer component containing an aromatic vinyl compound and a vinyl cyanide compound, and an initiator as necessary, are added to the system containing the core particles, and the monomer component is copolymerized in the presence of the core particles to form a shell layer that covers the core particles, thereby obtaining the core-shell type graft copolymer particles.

[0071] After the core-shell type graft copolymer particles are formed, one or more coagulants selected from the group consisting of acids and salts are added to the latex to coagulate it, and the latex is then heat-treated at a temperature of, for example, 40° C. or higher and 110° C. or lower, washed and dehydrated, dried, and sieved through a sieve of a predetermined size to separate the core-shell type graft copolymer particles.

[0072] A preferred embodiment of the process for producing the core-shell type graft copolymer particles will be described below with reference to Fig. 1. Fig. 1 shows the case where the rubber particles have a three-layer structure. First, a rubber particle core layer 11 made of an acrylic rubber is formed by emulsion polymerization. Next, as a second layer, a rubber particle intermediate layer 12 having a higher degree of cross-linking than the rubber particle core layer 11 is formed. Furthermore, as a third layer, a rubber particle surface layer 13 having a higher degree of cross-linking than the rubber particle intermediate layer 12 is formed, thereby forming a rubber particle 21 with a three-layer structure. Next, an acid group-containing polymer latex is added to the system containing the rubber particles 21 of the three-layer structure to cause the rubber particles 21 to coagulate and swell, thereby obtaining coagulated and swelled rubber particles 22. Furthermore, in a system containing the agglomerated enlarged particle 22 of rubber particles, a rubber outer layer 14 is formed as a fourth layer, thereby obtaining a core particle 23 composed of the agglomerated enlarged particle 22 and the rubber outer layer 14. Then, by graft polymerizing the shell layer 15 onto the core particle 23, the core-shell type graft copolymer particle 24 can be obtained.

[0073] <Resin composition> By blending the core-shell type graft copolymer particles according to the present disclosure with a thermoplastic resin to form a resin composition, the impact resistance of the thermoplastic resin can be specifically improved. The core-shell type graft copolymer particles according to the present disclosure are sufficiently separated from each other in the thermoplastic resin matrix resin, and can exhibit extremely good dispersibility. Furthermore, in the matrix resin, each graft copolymer particle can be significantly deformed to have a flat shape. Since conventionally known core-shell type particles have an almost spherical shape in the matrix resin, the core-shell type graft copolymer particles according to the present disclosure are considered to have extremely high flexibility. It is considered that the combination of these physical properties leads to a specific improvement in impact resistance by blending the core-shell type graft copolymer particles according to the present disclosure. However, the core-shell type graft copolymer particles and resin composition according to the present disclosure are not limited to the above description.

[0074] The thermoplastic resin is preferably a thermoplastic resin which is a copolymer containing an aromatic vinyl compound unit and a vinyl cyanide compound unit. The aromatic vinyl compound constituting the thermoplastic resin is not particularly limited, and examples thereof include styrene, α-methylstyrene, p-methylstyrene, p-isopropylstyrene, o-chlorostyrene, p-chlorostyrene, dichlorostyrene, etc. These may be used alone or in combination of two or more. Among these, styrene and α-methylstyrene are preferred, and styrene is particularly preferred.

[0075] The vinyl cyanide compound constituting the thermoplastic resin is not particularly limited, but examples thereof include acrylonitrile, methacrylonitrile, etc. These may be used alone or in combination of two or more. Acrylonitrile is preferred.

[0076] The thermoplastic resin may be a copolymer composed only of aromatic vinyl compound units and vinyl cyanide compound units, or may be a copolymer containing other copolymerizable vinyl compound units in addition to these two types of units.

[0077] The other copolymerizable vinyl compounds are not particularly limited, and examples thereof include (meth)acrylic acid alkyl esters having an alkyl group having 1 to 12 carbon atoms, such as methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate, maleimide compounds such as maleimide, N-phenylmaleimide, and cyclohexylmaleimide, acrylic acid, methacrylic acid, isopropenylnaphthalene, acrylamide, methacrylamide, glycidyl acrylate, and glycidyl methacrylate. These compounds may be used alone or in combination of two or more.

[0078] The content of the aromatic vinyl compound in the thermoplastic resin is not particularly limited, but is preferably 60 to 85% by weight, more preferably 65 to 80% by weight. The content of the vinyl cyanide compound is also not particularly limited, but is preferably 15 to 40% by weight, more preferably 20 to 35% by weight. The content of the other copolymerizable vinyl compound is also not particularly limited, but is preferably 0 to 25% by weight, more preferably 0 to 15% by weight.

[0079] Specific examples of the thermoplastic resin include styrene-acrylonitrile copolymer, α-methylstyrene-acrylonitrile copolymer, styrene-α-methylstyrene-acrylonitrile copolymer, styrene-maleimide-acrylonitrile copolymer, styrene-α-methylstyrene-maleimide-acrylonitrile copolymer, styrene-acrylonitrile-methyl methacrylate copolymer, α-methylstyrene-acrylonitrile-methyl methacrylate copolymer, styrene-α-methylstyrene-acrylonitrile-methyl methacrylate copolymer, styrene-maleimide-acrylonitrile-methyl methacrylate copolymer, styrene-α-methylstyrene-maleimide-acrylonitrile-methyl methacrylate copolymer, styrene-α-methylstyrene-maleimide-acrylonitrile-methyl methacrylate copolymer, etc. These may be used alone or in combination of two or more.

[0080] From the viewpoint of improving impact resistance, the content of the core-shell type graft copolymer particles in the resin composition is preferably 10 to 100 parts by weight, more preferably 15 to 80 parts by weight, even more preferably 20 to 60 parts by weight, and particularly preferably 25 to 50 parts by weight, relative to 100 parts by weight of the thermoplastic resin.

[0081] The resin composition may further contain a thermoplastic resin other than the above-mentioned thermoplastic resin. Such a thermoplastic resin is not particularly limited, but may be, for example, an acrylic resin such as polymethyl methacrylic acid, a vinyl chloride resin, a polycarbonate resin, an amide resin, a polyester resin, etc. These may be used alone or in combination of two or more kinds.

[0082] The resin composition may be appropriately blended with flame retardants, antibacterial agents, release agents, nucleating agents, plasticizers, antioxidants, heat stabilizers, light stabilizers, UV absorbers, compatibilizers, pigments, dyes, antistatic agents, lubricants, etc., as necessary. The blending amount of each additive can be appropriately determined by those skilled in the art. These may be used alone or in combination of two or more.

[0083] In particular, phenol-based, sulfur-based, phosphorus-based, and hindered amine-based antioxidants or stabilizers; benzophenone-based and benzotriazole-based ultraviolet absorbers; and internal and external lubricants such as organopolysiloxanes, aliphatic hydrocarbons, esters of higher fatty acids and higher alcohols, amides or bisamides of higher fatty acids and modified products thereof, oligoamides, and metal salts of higher fatty acids can be suitably added.

[0084] The resin composition can be produced, for example, by mixing the core-shell graft copolymer particles and the thermoplastic resin in the form of latex, slurry, solution, powder, pellets, or a combination thereof. When the core-shell graft copolymer particles and the thermoplastic resin are in the form of latex, for example, an alkaline earth metal salt such as calcium chloride, magnesium chloride, or magnesium sulfate, an alkali metal salt such as sodium chloride or sodium sulfate, or an inorganic or organic acid such as hydrochloric acid, sulfuric acid, phosphoric acid, or acetic acid may be added to the latex to coagulate the latex into a slurry, and then the slurry may be dehydrated and dried. A spray drying method may also be used. In this case, a part of the additive such as a stabilizer may be added to the latex or slurry in the form of a dispersion.

[0085] The resin composition can be prepared by blending any additives as necessary with the core-shell graft copolymer particles and the powder or pellets of the thermoplastic resin, kneading the mixture in a known melt kneader such as a Banbury mixer, a roll mill, a single-screw extruder or a twin-screw extruder, and shaping the mixture into a desired molded product by a known molding method such as injection molding, extrusion molding or blow molding.

[0086] The resin composition can be used in various applications such as electrical and electronic applications, architectural applications, and vehicle applications. Specifically, the resin composition can be used in electrical and electronic applications such as personal computers, liquid crystal displays, projectors, PDAs, printers, copy machines, fax machines, video cameras, digital cameras, mobile phones (smartphones), portable audio devices, game consoles, DVD recorders, microwave ovens, and rice cookers; architectural applications such as road light-transmitting panels, skylights, carports, lighting lenses, lighting covers, building material sizing, and doors; and vehicle applications such as steering wheels, shift levers, and vibration-proof materials for automobiles and trains, displays, lighting, and driver's seat panels. EXAMPLES

[0087] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, "parts" and "%" refer to "parts by weight" and "% by weight" unless otherwise specified.

[0088] (Method of measuring the average particle size of polymer particles) The average particle size of the polymer particles was measured as a volume average particle size in the state of the polymer particle latex. The measuring device used was Nanotrac Wave manufactured by Nikkiso Co., Ltd. The calculation mode was set to the UPA compatible mode.

[0089] (Synthesis Example 1) <Production of Acid Group-Containing Polymer Latex> 2836g of deionized water and 180g of 2% sodium dialkyl sulfosuccinate ("Pelex OT-P" manufactured by Kao Corporation) were added to an 8L polymerization vessel, the temperature was raised to 70℃, and nitrogen was flowed in. A solution of 59.2g of styrene, 40.8g of butyl acrylate, 0.22g of 52% p-menthane hydroperoxide, 0.0015g of ferrous sulfate (FeSO4·7H2O), and 0.025g of disodium ethylenediaminetetraacetate in 8.0g of deionized water was added, 50g of deionized water was added, and 48g of 5% sodium formaldehyde sulfoxylate (hereinafter also referred to as "Rongalit") was added to start polymerization.

[0090] After 30 minutes, 80g of 5% Rongalit was added, and a mixture of 236.8g of styrene, 163.2g of butyl acrylate, 2.5g of t-butyl mercaptan, and 0.92g of 52% p-menthane hydroperoxide was added over 70 minutes, followed by 50g of deionized water. After 10 minutes, a mixture of 808g of styrene, 392g of butyl acrylate, 300g of methacrylic acid, and 7.5g of t-butyl mercaptan was added over 210 minutes. Rongalit and p-menthane hydroperoxide were appropriately added to obtain an acid group-containing polymer latex with a conversion rate of 99.9%, a solid content concentration of 31.5%, and a volume average particle size of 200nm.

[0091] Example 1 <Production of graft copolymer latex> (rubber particles) 3400 g of deionized water, 64.3 g of potassium hydroxide saponification product of 15.6% beef tallow fatty acid (LUNAC TH manufactured by Kao Corporation), and 50 g of 2% sodium carbonate were charged into an 8 L polymerization reactor, heated to 50° C., and nitrogen was flowed through.

[0092] A mixture of 100 g of butyl acrylate, 0.125 g of allyl methacrylate, and 0.26 g of 69% t-butyl hydroperoxide was added to the polymerization reactor, a solution of 0.0108 g of ferrous sulfate (FeSO4·7H2O) and 0.018 g of disodium ethylenediaminetetraacetate dissolved in 5.7 g of deionized water was added, and 32.0 g of 5% Rongalit was added, followed by stirring for 30 minutes.

[0093] The following beakers (i) and (ii) were prepared. Beaker (i): 0.125% solution of allyl methacrylate in butyl acrylate: a mixture of 660 g of butyl acrylate, 0.825 g of allyl methacrylate, and 1.7 g of 69% t-butyl hydroperoxide Beaker (ii): 0.5% solution of allyl methacrylate in butyl acrylate: a mixture of 540 g of butyl acrylate, 2.7 g of allyl methacrylate, and 1.4 g of 69% t-butyl hydroperoxide.

[0094] The solution from beaker (ii) was added to beaker (i) at a rate of 3.0 g / min over a period of 3 hours, and beaker (i) was stirred. At the same time, the solution from beaker (i) was added to the polymerizer at a rate of 6.7 g / min over a period of 3 hours (this operation was performed so that the ratio of allyl methacrylate to butyl acrylate increased linearly from 0.125% to 0.5% over a period of 3 hours). At 10, 20, 40, and 60 minutes after the start of monomer addition, 7.7 g of potassium hydroxide saponification product of 15.6% beef tallow fatty acid (LUNAC TH, Kao Corporation) was added. This resulted in the formation of rubber particles, in which the degree of crosslinking increases continuously from the center to the surface.

[0095] (agglomerated hypertrophy) Thirty minutes after the monomer addition was completed, 30 g of a 2% aqueous sodium hydroxide solution was added, 185.8 g of the acid group-containing polymer latex having a solid content concentration of 31.5% was added, and 200 g of a 2% aqueous sodium hydroxide solution was added, followed by stirring for 60 minutes. This resulted in the formation of aggregated and enlarged rubber particles.

[0096] (Rubber outer layer) A solution of 0.015 g of ferrous sulfate (FeSO4·7H2O) and 0.025 g of disodium ethylenediaminetetraacetate dissolved in 8.0 g of deionized water was added, followed by 40.0 g of 5% Rongalite and stirring for 30 minutes. A mixture of 100g of butyl acrylate, 9.0g of allyl methacrylate, and 0.29g of 69% t-butyl hydroperoxide was added over 15 minutes, and 0.35g of 69% t-butyl hydroperoxide was added and stirred for 30 minutes. This formed a rubber outer layer, and core particles were obtained. The particle diameter of the core particles was 700nm.

[0097] (Shell layer) A mixture of 450.0 g of styrene, 150 g of acrylonitrile, and 4.4 g of 69% t-butyl hydroperoxide was added over 120 minutes. A shell layer was formed by adding t-butyl hydroperoxide and Rongalite appropriately, and a graft copolymer latex with a conversion rate of 100% and a solid content concentration of 32.3% was obtained.

[0098] Example 2 <Production of graft copolymer latex> (Rubber particle core layer) 3400 g of deionized water, 64.3 g of potassium hydroxide saponification product of 15.6% beef tallow fatty acid (LUNAC TH manufactured by Kao Corporation), and 50 g of 2% sodium carbonate were charged into an 8 L polymerization reactor, heated to 50° C., and nitrogen was flowed through.

[0099] A mixture of 100g of butyl acrylate, 0.125g of allyl methacrylate, and 0.26g of 69% t-butyl hydroperoxide was added to the polymerization reactor, a solution of 0.0108g of ferrous sulfate (FeSO4·7H2O) and 0.018g of disodium ethylenediaminetetraacetate dissolved in 5.7g of deionized water was added, 32.0g of 5% Rongalit was added, and the mixture was stirred for 30 minutes. The particle size was 35nm. Then, a mixture of 400g of butyl acrylate, 0.5g of allyl methacrylate, and 1.0g of 69% t-butyl hydroperoxide was added over 60 minutes. This formed particles that correspond to the central layer of the rubber particles.

[0100] (rubber particle intermediate layer) A mixture of 400 g of butyl acrylate, 1.0 g of allyl methacrylate, and 1.0 g of 69% t-butyl hydroperoxide was added over 60 minutes to form a rubber particle intermediate layer.

[0101] (rubber particle surface layer) A mixture of 400g of butyl acrylate, 2.0g of allyl methacrylate, and 1.0g of 69% t-butyl hydroperoxide was added over 60 minutes and stirred for 30 minutes. This formed a rubber particle surface layer, and rubber particles with a three-layer structure consisting of a rubber particle center layer, a rubber particle middle layer, and a rubber particle surface layer were obtained. The particle diameter of the rubber particles was 85 nm. In the rubber particles, the degree of crosslinking increases in the order of the rubber particle center layer, the rubber particle middle layer, and the rubber particle surface layer.

[0102] (agglomerated hypertrophy) 30 g of a 2% aqueous sodium hydroxide solution was added, 185.8 g of the acid group-containing polymer latex having a solid content concentration of 31.5% was added, and 200 g of a 2% aqueous sodium hydroxide solution was added, thereby obtaining aggregated and enlarged particles of rubber particles.

[0103] (Rubber outer layer) After 60 minutes, a solution of 0.015 g of ferrous sulfate (FeSO4·7H2O) and 0.025 g of disodium ethylenediaminetetraacetate dissolved in 8.0 g of deionized water was added, followed by 40.0 g of 5% Rongalit and stirring for 30 minutes. A mixture of 100g of butyl acrylate, 9.0g of allyl methacrylate, and 0.29g of 69% t-butyl hydroperoxide was added over 15 minutes, and 0.35g of 69% t-butyl hydroperoxide was added and stirred for 30 minutes. This formed a rubber outer layer, and core particles were obtained. The particle diameter of the core particles was 700nm.

[0104] (Shell layer) A mixture of 450.0 g of styrene, 150 g of acrylonitrile, and 4.4 g of 69% t-butyl hydroperoxide was added over 120 minutes. A shell layer was formed by adding t-butyl hydroperoxide and Rongalite appropriately, and a graft copolymer latex with a conversion rate of 100% and a solid content concentration of 32.0% was obtained.

[0105] <Graft copolymer granulation> Each graft copolymer latex obtained above was heated to 70°C, and an aqueous calcium chloride solution was added to make a slurry, which was then dehydrated in a centrifugal dehydrator, washed with deionized water, and dried at 50°C for 2 days to obtain a powder of each graft copolymer.

[0106] (Example 3 and Comparative Examples 1 to 12) In Example 3, a powder of a graft copolymer was obtained in the same manner as in Example 2, except that the composition was changed according to the description in Table 1. In Comparative Examples 1 to 6, graft copolymer powders were obtained in the same manner as in Example 2, except that the composition was changed according to the description in Table 1 and the amount of the initial potassium hydroxide saponification product of beef tallow fatty acid was adjusted to adjust the core particle diameter. In Comparative Examples 7 to 10, graft copolymer powders were obtained in the same manner as in Example 2, except that the compositions were changed according to the descriptions in Table 1. In Comparative Examples 11 and 12, graft copolymer powders were obtained in the same manner as in Example 2, except that the composition was changed according to the description in Table 1 and the time when the aggregation and thickening was carried out was changed.

[0107] (Method of measuring Izod impact strength) 700 g of the obtained graft copolymer powder, 1293 g of AS resin (PN-117, manufactured by Chimei Co., Ltd.), and 12 g of carbon black master batch (AS resin containing 40% carbon black) were added, extruded with an extruder to obtain extruded pellets, which were then injected into an injection mold to obtain 3 mm 1 / 8 inch bars. The notched Izod impact strength was measured at 23°C in accordance with JIS K-7110. The results are shown in Table 1.

[0108] [Table 1]

[0109] In the table, BA stands for butyl acrylate, and ALMA stands for allyl methacrylate. The amount of each monomer is shown in parts by weight, with the total amount of monomers used in the entire graft copolymer being 100 parts by weight. Meanwhile, the amount of ALMA is shown as a percentage of the amount of monomer used in each layer.

[0110] It is apparent from Table 1 that Examples 1 to 3 have extremely large Izod impact strength values ​​and are excellent in impact resistance as compared with Comparative Examples 1 to 12. In addition, in Examples 1 to 3, core-shell graft copolymer particles were used in which rubber particles having a higher degree of crosslinking on the surface than inside were aggregated and enlarged, a rubber outer layer was formed to obtain core particles, and a shell layer was further provided. On the other hand, in Comparative Examples 1 to 3, the degree of crosslinking of the rubber particles is uniform, and the coagulation thickening of the rubber particles is not performed. In Comparative Examples 4 to 6, the coagulation thickening of the rubber particles is not performed. In Comparative Examples 7 to 9, the degree of crosslinking of the rubber particles is uniform. In Comparative Example 10, the degree of crosslinking of the rubber particles is uniform, and a rubber outer layer is not formed. In Comparative Example 11, the degree of crosslinking of the rubber particles is uniform, and the coagulation thickening of the rubber particles is not performed, and the coagulation thickening of the core particles is performed after the formation of the rubber outer layer. In Comparative Example 12, the coagulation thickening of the rubber particles is not performed, and the coagulation thickening of the core particles is performed after the formation of the rubber outer layer. [Explanation of symbols]

[0111] 11 Rubber particle core layer 12 Rubber particle intermediate layer 13 Rubber particle surface layer 14 Rubber outer layer 15 Shell Layer 21 Rubber particles 22. Agglomerated rubber particles 23 Core Particle 24 Core-shell type graft copolymer particles

Claims

1. A core-shell type graft copolymer particle comprising a core particle and a shell layer covering the core particle, The core particle includes an agglomerated thickening particle of rubber particles and a rubber outer layer covering the agglomerated thickening particle, The rubber particles are configured so that the degree of cross-linking at the surface of the particle is higher than the degree of cross-linking at the interior of the particle, The aggregated and enlarged particles are formed by aggregating and enlarging the rubber particles with an acid group-containing polymer, the rubber particles and the outer rubber layer are each formed from an acrylic rubber obtained by polymerizing a monomer component containing an acrylic monomer and a crosslinkable monomer, The core-shell type graft copolymer particles, wherein the shell layer is formed from a copolymer containing an aromatic vinyl compound unit and a vinyl cyanide compound unit.

2. 2. The core-shell type graft copolymer particle according to claim 1, wherein the rubber particle is configured so that the degree of cross-linking increases from the center of the particle toward the surface.

3. The rubber particle includes a rubber particle core layer located at the center of the particle, and a rubber particle surface layer located on the surface of the particle, 2. The core-shell type graft copolymer particle according to claim 1, wherein the surface layer of the rubber particle has a higher degree of crosslinking than the center layer of the rubber particle.

4. The core-shell type graft copolymer particle according to claim 3 , wherein the rubber particle further comprises a rubber particle intermediate layer located between the rubber particle central layer and the rubber particle surface layer.

5. 5. The core-shell type graft copolymer particle according to claim 1, wherein the acid group-containing polymer is a polymer containing a carboxyl group-containing vinyl monomer unit.

6. 6. The core-shell graft copolymer particle according to claim 1, wherein the ratio of the core particles to the core-shell graft copolymer particles is 66 to 90% by weight.

7. The core-shell type graft copolymer particle according to any one of claims 1 to 6, wherein the volume average particle diameter of the core particle is 400 to 1200 nm.

8. A method for producing core-shell graft copolymer particles comprising a core particle and a shell layer covering the core particle, comprising the steps of: A step of polymerizing a monomer component including an acrylic monomer and a crosslinkable monomer to form rubber particles configured such that the degree of crosslinking on the surface of the particles is higher than the degree of crosslinking inside the particles; a step of aggregating and enlarging the rubber particles with an acid group-containing polymer latex to obtain aggregated and enlarged particles of the rubber particles; a step of polymerizing a monomer component including an acrylic monomer and a crosslinkable monomer in the presence of the agglomerated thickened particles to form a rubber outer layer covering the agglomerated thickened particles, thereby obtaining a core particle including the agglomerated thickened particles and the rubber outer layer; a step of copolymerizing a monomer component containing an aromatic vinyl compound and a vinyl cyanide compound in the presence of the core particle to form a shell layer covering the core particle, thereby obtaining the core-shell graft copolymer particle.

9. 9. The method for producing core-shell graft copolymer particles according to claim 8, wherein in the step of forming the rubber particles, a ratio of the crosslinkable monomer to the monomer component is increased over time to form rubber particles having a higher degree of crosslinking from the center of the rubber particles toward the surface.

10. 9. The method for producing core-shell type graft copolymer particles according to claim 8, wherein in the step of forming the rubber particles, a monomer component containing an acrylic monomer and a crosslinkable monomer are multistage-polymerized to form rubber particles including a rubber particle central layer and a rubber particle surface layer having a higher degree of crosslinking than the rubber particle central layer.

11. The method for producing core-shell type graft copolymer particles according to any one of claims 8 to 10, wherein the acid group-containing polymer is a polymer containing a carboxyl group-containing vinyl monomer unit.

12. 100 parts by weight of a thermoplastic resin which is a copolymer containing an aromatic vinyl compound unit and a vinyl cyanide compound unit; and A resin composition comprising 10 to 100 parts by weight of the core-shell type graft copolymer particles according to any one of claims 1 to 7.

13. A molded article obtained by molding the resin composition according to claim 12.

Citation Information

Patent Citations

  • Thermoplastic resin composition

    JP1983222139A

  • Multilayer graft copolymer

    JP1992146910A

  • Multilayered acrylic polymer particle, its production, and its use

    JP1995138328A

  • Thermoplastic resin composition

    JP1998077383A

  • Styrene resin composition with excellent impact resistance and colorability

    JP2013221116A